Investigating stigma attitudes towards people with mental illness among residents and house officers: an Egyptian study - Abeer M. Eissa; Mahmoud M. Elhabiby; Doha El Serafi; Hanan H. Elrassas; Eman M. Shorub; Alaa A. El-Madani (Middle East Current Psychiatry, 2020)
Abstract Background Stigma is a basic component of the negative discrimination that people with mental illness experience every day. It blocks access to facilities that have been created to help people with mental illness. Furthermore, the attitudes held by people with authority (including clinical staff and officers) towards people with mental illness are likely to influence their attitude towards them and hence the experience and treatment outcome of the patients. The aim of this work is to study and compare the attitudes of Egyptian residents of different clinical specialties and house officers towards patients with mental illness. The current study aimed to study the attitudes of Egyptian medical residents and house officers towards patients with mental illness and compare between both groups. This cross-sectional comparative study was designed to assess 150 residents and 201 house officers at Ain Shams University Hospitals by using the Mental Illness Clinician Attitude Scale version 4 (MICA-4) and newly designed questions related to stigma. Results The study revealed that the scores of MICA questionnaire were significantly lower than the cut point for negative attitude in both residents and house officers (P < 0.0001). In addition, there was a trend of an increase in MICA scores throughout the three levels of seniority but with no statistically significant difference. Furthermore, there was no statistical significant finding regarding the majority of MICA items or stigma sheet questions across the different specialties. Conclusion Stigma is one of the most disabling factors that prevent people with mental illness to live a normal social and occupational life and thus receive a good quality of life and equal chance of medical health care as other non-psychiatric patients.